2010
DOI: 10.1016/j.neurobiolaging.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of neurodegeneration in brains of older adults who do not yet fulfill MCI criteria

Abstract: We sought to determine whether there are structural and metabolic changes in the brains of older adults with cognitive complaints yet who do not meet MCI criteria (i.e., preMCI). We compared the volumes of regional lobar gray matter (GM) and medial temporal lobe structures, including the hippocampus, entorhinal cortex (ERC), fusiform and parahippocampal gyri, and metabolite ratios from the posterior cingulate in individuals who had a Clinical Demetia Rating (CDR) of 0.5, but who did not meet MCI criteria (preM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 76 publications
(83 reference statements)
3
38
0
Order By: Relevance
“…We found an increase in amyloid deposition and abnormal levels of CSF amyloid and tau in older adults with SMC, which was strongly associated with APOE ε4 carrier status. However, we did not observe differences in glucose metabolism and MTL atrophy in this population, even in SMC APOE ε4+, as has been previously reported [4, 13, 17, 19, 21, 23, 28, 46, 47]. Given the previous research in participants with SCD/SMC, the lack of hypometabolism or atrophy is somewhat surprising.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found an increase in amyloid deposition and abnormal levels of CSF amyloid and tau in older adults with SMC, which was strongly associated with APOE ε4 carrier status. However, we did not observe differences in glucose metabolism and MTL atrophy in this population, even in SMC APOE ε4+, as has been previously reported [4, 13, 17, 19, 21, 23, 28, 46, 47]. Given the previous research in participants with SCD/SMC, the lack of hypometabolism or atrophy is somewhat surprising.…”
Section: Discussionsupporting
confidence: 78%
“…In the Alzheimer’s Disease Neuroimaging Initiative (ADNI), a comparable group of older adults were recruited with significant memory concerns (SMC) in form of self-only complaints exceeding a predefined cut-off score on memory ratings. Previous studies have shown that older adults with SCD/SMC have an increased risk for future progression to AD [516], as well as AD-like changes in neuroimaging and cerebrospinal fluid (CSF) biomarkers [4, 13, 1727]. In addition, SCD/SMC participants who are carriers of the most commonly reported genetic variant associated with late onset AD, the apolipoprotein E ( APOE) ε4 allele, show greater medial temporal lobe (MTL) hypometabolism and atrophy, increased cerebral amyloid, as well as altered CSF measures of amyloid and tau [22, 23, 28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that decreased NAA concentrations reflect reduced neuronal density or neuronal function 19, 21 . Both reasons could be responsible for our observations of age-related [NAA] reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes occur in the brain, and Alzheimer's disease (AD)-related pathology can be seen even prior to diagnosis of MCI. [1][2][3][4] Early identification of individuals at risk of cognitive decline is important in order to implement appropriate treatments early in the disease process.…”
Section: Introductionmentioning
confidence: 99%